VUCA leadership skills in implementing distance learning amidst COVID-19 pandemic - Estillore, Micah Jane A. (Animo Repository, 2022)
The COVID-19 pandemic caused massive school closures, leading to mandatory Distance Learning (DL) implementation. This sudden and drastic transition brought more volatility, uncertainty, complexity, and ambiguity to an already VUCA educational landscape. Thence, the researcher aimed to explore how VUCA leadership skills became relevant in the implementation of DL in private schools during the said global crisis. Using a case study qualitative approach, three educational leaders in private schools in Zambales were examined through a series of interviews and parallel interviews with two teacher-coordinators in each of their respective schools. The findings of the study revealed that agility, dilemma flipping, vision/clarity, and collaboration were all noted to be relevant VUCA skills in the school’s success in implementing DL during the pandemic. Aside from the main VUCA skills, the data revealed the distinct strengths of each case. Principal A’s unique feature was the highlight of their school’s identity as a Catholic educational institution; using faith as a stronghold to overcome challenges and drive to pursue opportunities. Principal B’s strength lay in the firm leadership that served as the solid basis for the school's resilience against dilemmas; while Principal C thrived on unexpected wins and positive transformation as they embraced new pedagogical approaches and digital tools during the crisis. The study recommends that educational leaders learn from the DL experience and begin to intentionally hone and exercise the VUCA skills; for the educational scene will be considerably more VUCA in the future. Furthermore, educational organizations and authorities are recommended to create avenues where schools could collaborate and share best practices in navigating VUCA and improving DL, better prepared for the future.